2022
DOI: 10.3389/fendo.2022.961748
|View full text |Cite
|
Sign up to set email alerts
|

Copper deposition in Wilson’s disease causes male fertility decline by impairing reproductive hormone release through inducing apoptosis and inhibiting ERK signal in hypothalamic-pituitary of mice

Abstract: Wilson’s disease (WD) is an autosomal recessive disorder of copper metabolism characterized by liver and central nervous system dysfunction. Considerable evidence suggests that infertility is also very common in male patients with WD, but the exact molecular mechanisms involved remain unknown. In order to further investigate the pathological changes in the hypothalamic-pituitary-testicular (HPT) axis and its mechanisms, mice were divided into the normal control group (NC), WD model TX mice group (WD), dimercap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The disease is characterized by hepatic and neurological de cits as the main clinical manifestations. 12,13 Since COVID-19 can also present with hepatic and neurological damage, 7,8,9 it is necessary for patients with WD to pay attention to the prevention of SARS-CoV-2 infection to avoid the risk of possible exacerbation after infection.…”
Section: Introductionmentioning
confidence: 99%
“…The disease is characterized by hepatic and neurological de cits as the main clinical manifestations. 12,13 Since COVID-19 can also present with hepatic and neurological damage, 7,8,9 it is necessary for patients with WD to pay attention to the prevention of SARS-CoV-2 infection to avoid the risk of possible exacerbation after infection.…”
Section: Introductionmentioning
confidence: 99%
“…The disease is characterized by hepatic and neurological de cits as the main clinical manifestations. 12,13 As COVID-19 can also present with hepatic and neurological damage, 7,8,9 it is necessary for patients with WD to pay attention to the prevention of SARS-CoV-2 infection to avoid the risk of possible exacerbation after infection.…”
Section: Introductionmentioning
confidence: 99%
“…Logistic regression analysis showed that vaccination against SARS-CoV-2 was not signi cantly associated with increased UWDRS scores. The safety analysis demonstrated that 21.2% had post-vaccination adverse events.Conclusions: In this study, vaccination against SARS-CoV-2 was safe in WD patients, providing evidence for the safety of vaccination in WD patients.The disease is characterized by hepatic and neurological de cits as the main clinical manifestations [12][13] . As COVID-19 can also present with hepatic and neurological damage [7][8][9] , it is necessary for patients with WD to pay attention to the prevention of SARS-CoV-2 infection to avoid the risk of possible exacerbation after infection.Administering COVID-19 vaccines provided limited protection against SARS-CoV-2 infection across all age groups but high protection against severe/critical illness and COVID-19-related death [14] .…”
mentioning
confidence: 99%